2016
DOI: 10.14202/vetworld.2016.260-268
|View full text |Cite
|
Sign up to set email alerts
|

Impact of heat stress on health and performance of dairy animals: A review

Abstract: Sustainability in livestock production system is largely affected by climate change. An imbalance between metabolic heat production inside the animal body and its dissipation to the surroundings results to heat stress (HS) under high air temperature and humid climates. The foremost reaction of animals under thermal weather is increases in respiration rate, rectal temperature and heart rate. It directly affect feed intake thereby, reduces growth rate, milk yield, reproductive performance, and even death in extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
259
0
19

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(333 citation statements)
references
References 64 publications
11
259
0
19
Order By: Relevance
“…Regarding the respiratory rate (Table-3), there was no significant difference between species and both species attended the highest respiratory rates in the last week prepartum which is compatible with the results of THI and RT. HS significantly affected respiratory rate (breaths/min) when compared to normal values (76.8 and 77.8 vs. 40-50) for cow and buffalo, respectively, as presented by Das et al [26]. According to Dalcin et al, respiratory rate can be a relevant physiological indicator for HS [27].…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Regarding the respiratory rate (Table-3), there was no significant difference between species and both species attended the highest respiratory rates in the last week prepartum which is compatible with the results of THI and RT. HS significantly affected respiratory rate (breaths/min) when compared to normal values (76.8 and 77.8 vs. 40-50) for cow and buffalo, respectively, as presented by Das et al [26]. According to Dalcin et al, respiratory rate can be a relevant physiological indicator for HS [27].…”
Section: Resultsmentioning
confidence: 79%
“…There is a very high positive correlation between the respiratory rate and ambient temperature. The increase in breathing rate (panting) sharply increases the loss of CO 2 through pulmonary ventilation with upsetting the critical balance of carbonic acid to bicarbonate excretion causing respiratory alkalosis [26]. In cattle under heat load, about 15% of the endogenous heat is lost directly from the body core through the respiratory tract [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were reported by Indu [12] in Tharparkar and KF calves when the calves were exposed at 44°C for 4 h in a climatic chamber. Das et al [13] reported that air temperatures above 20-25°C in temperate climate and 25-37°C in a tropical climate such as in India, enhance heat gain beyond that lost from the body and induce HS which results into increased body surface temperature, RR, heart rate, and RT which leads to decrease in feed intake, production, and reproductive efficiency of animals. Similar findings were reported in Holstein Friesian and Brown Swiss cattle when cows were exposed to 0.45% of CO 2 level [6].…”
Section: Physiological Responsesmentioning
confidence: 99%
“…Rising temperature can increase heat stresses, illness, diseases, and mortality, which subsequently reduce the productivity of livestock (Na rdone et al 2010; R ojas-Downing et al 2017; Das et al 2016). Increased temperatures will promote the growth of some forage crops but decrease nutrient availability (Rojas-Downing et al 2017;IPCC 2007).…”
Section: Climate Change Impacts On Florida's Livestock Productionmentioning
confidence: 99%